Analisis Media Sosial dalam Peningkatan Pemasaran Global - Yulie Aisyah Binrany; Olivia Theresia Manurung; Christian Putra Tarigan; Lenti Susanna Saragih; Aurora Elise Putriku (Pusat Riset dan Inovasi Nasional, 2024)
Social media has an increasingly important role in global marketing strategies in today's digital era. This research aims to analyze the impact of social media, especially e-commerce, in improving global marketing. Using literature study and online research methods, this research explores the role of social media in increasing global market access, building global brand awareness, influencing consumer behavior, supporting data-based marketing strategies, and achieving higher marketing efficiency. The results show that social media is not only a promotional tool, but also a key player in global digital business transformation, providing opportunities for companies to grow and compete in an increasingly digitally connected global market.